Diversity analysis of Plio-Pleistocene large mammal communities in the Omo-Turkana Basin, eastern Africa. Issue 124 (November 2018) - Du, Andrew; Alemseged, Zeresenay
Abstract: Knowing how the diversity of large mammal communities changes across space and time provides an important ecological framework for studying hominin evolution. However, diversity studies that apply methods currently used by neoecologists are rare in paleoanthropology and are also challenging due to diversity's unusual statistical properties. Here, we apply up-to-date analytical methods for understanding how species- and genus-level large mammalian diversity in the Omo-Turkana Basin changed through time and across space at multiple spatiotemporal scales (within each formation:10 2−3 km 2 and 10 4−5 years; and within the basin as a whole: 10 3 km 2 and 10 5 years). We found that, on average, Koobi Fora's large mammal community was more diverse than Nachukui's, which in turn was more diverse than Shungura's. Diversity was stable through time within each of these formations (alpha diversity), as was diversity in the basin as a whole (gamma diversity). Compositional dissimilarity between these three formations (beta diversity) was relatively low through time, with a 0.6 average proportion of shared species, suggesting dispersal acted to homogenize the region. Though alpha and gamma diversity were fairly stable through time, we do observe several notable peaks: during the KBS Member in Koobi Fora (30% increase), the Lokalalei Member in Nachukui (120% increase), and at 1.7 Ma in the entire basin (100% increase). We conclude by (1) demonstrating that habitat heterogeneity was an important factor influencing alpha diversity within each of the three formations, and (2) hypothesizing that diversity stability may have been driven by equilibrial dynamics in which overall diversity was constrained by resource availability, implying biotic interactions were an important factor in structuring the communities that included hominins as members. Our findings demonstrate the need to quantify how large mammal diversity changes across time and space in order to further our understanding of hominin ecology and evolution.